Sunset cluster : a shortline railroad saga - Grant, H. Roger, 1943- (Railroads Past and Present Series., 2023)
"Discover the Sunset Cluster-railroads that were doomed to fail? The first two decades of the 20th century were the twilight of the railroad age. Major routes had long been established, and local service became the focus of new construction. Beginning in 1907, a cluster of five shortline railroads were established in otherwise unconnected parts of Iowa. By the dawn of the Great Depression, all these routes would be discontinued. The five Iowa 'sunset cluster' railroads might appear to deserve eternal obscurity, being at best minor footnotes to American railroad history. After all, their total mileage barely exceeded 100 miles. Their average life span, moreover, covered about five years, and the Des Moines & Red Oak Railway (DM&RO) never turned a wheel. Yet, to understand the rise of the railroad empires of the 19th century, it is necessary to study their fall. Using contemporary newspapers, government reports, and other little-known sources, renowned railway historian H. Roger Grant offers a fascinating look at these shortline railroads. Sunset Cluster explores the almost desperate desire by communities to benefit from steel rails before the regional railroad map finally imploded and the challenges faced by latter-day shortline builders"--